A novel remitting leukodystrophy associated with a variant in FBP2. Issue 2 (11th March 2021) - Gizak, Agnieszka; Diegmann, Susann; Dreha-Kulaczewski, Steffi; Wiśniewski, Janusz; Duda, Przemysław; Ohlenbusch, Andreas; Huppke, Brenda; Henneke, Marco; Höhne, Wolfgang; Altmüller, Janine; Thiele, Holger; Nürnberg, Peter; et al.
Abstract: Leukodystrophies are genetic disorders of cerebral white matter that almost exclusively have a progressive disease course. We became aware of three members of a family with a disorder characterized by a sudden loss of all previously acquired abilities around 1 year of age followed by almost complete recovery within 2 years. Cerebral MRI and myelin sensitive imaging showed a pronounced demyelination that progressed for several months despite signs of clinical improvement and was followed by remyelination. Exome sequencing did not-identify any mutations in known leukodystrophy genes but revealed a heterozygous variant in the FBP2 gene, c.343G>A, p. Val115Met, shared by the affected family members. Cerebral MRI of other family members demonstrated similar white matter abnormalities in all carriers of the variant in FBP2 . The FBP2 gene codes for muscle fructose 1, 6-bisphosphatase, an enzyme involved in gluconeogenesis that is highly expressed in brain tissue. Biochemical analysis showed that the variant has a dominant negative effect on enzymatic activity, substrate affinity, cooperativity and thermal stability. Moreover, it also affects the non-canonical functions of muscle fructose 1, 6-bisphosphatase involved in mitochondrial protection and regulation of several nuclear processes. In patients' fibroblasts, muscle fructose 1, 6-bisphosphatase shows no colocalization with mitochondria and nuclei leading to increased reactive oxygen species production and a disturbed mitochondrial network. In conclusion, the results of this study indicate that the variant in FBP2 disturbs cerebral energy metabolism and is associated with a novel remitting leukodystrophy. Abstract : Gizak et al. report on a novel remitting leukodystrophy associated with a variant in the FBP2 gene coding for muscle fructose 1, 6-bisphosphatase. The variant has a dominant negative effect not only on enzymatic properties and stability but also on non-canonical functions important for mitochondrial protection and regulation of nuclear processes. Graphical Abstract: